Assessment Seroprevalence of Toxocara Canis Antibodies among Children’s Outpatient with the Wheezing in Urban Public of Tehran - Agin, Kh (International Journal of Medical Toxicology and Forensic Medicine, 2012)
Background: Toxocariasis is a zoontic helminthes infection, occurring in human by the accidental ingestion of embryonated eggs of Toxocara canis (TC) and less frequently, Toxocara catis (TCC). Children are on the front line of encounter group. Clinical features may mimic respiratory symptoms as; asthma–like symptoms plus producing bronchial airway hyper-reactivity. The aim of this study was to determine seroprevalence of TC infection among children’s outpatient with the wheezing symptom among urban public of Tehran. Method: All of the children with current wheezing symptom that was coming in the chest clinic, sequentially enrolled as sample population. Diagnosis of known diseases associated with the wheezing was made possible. Anti TC Ig G antibodies in serum were measured based upon the recommendation commercial kit. Results: A total 89 children meet the study criteria. Mean age was 9.7±3.8 SD years, ranged 2-15 years. Boy/girl ratio was 1.2. Seropositive for TC antibody was 16%. TC infection was noticeable in boys subgroup 53%. Conclusion: Seroconvertion of TC infection was meaningful among children, 2-15 years in Tehran. School-aged group had been higher rated infection than other groups. Toxocariasis among children of target population was associated with eosinophilia and allergic reaction.